Caregivers' and adolescents' perceptions of a culturally adapted, evidence—based programme for substance-misusing teens - Chibambo, Vimbayinashe Sithembile (Department of Psychology, 2020)
Context – The prevalence of problem substance use is a global concern, particularly for adolescents due to their ongoing developmental changes. Amongst other contributory factors, parenting styles adopted by parents and caregivers can either; increase the risks of their children developing substance misuse problems or prevent its onset. Knowledge about the needs and experiences of the caregivers of adolescents who misuse substances is limited and greatly under-researched. Brief interventions (BIs) have been identified as an effective means of tackling this problem-type behaviour among adolescents, including ‘Teen Intervene', which was developed in the US. This evidence-based intervention included a parent component which has been found to further enhance the interventions' positive outcomes. Rationale – In light of the unique caregiver structures in South Africa, the general neglect of their needs in the South African literature with regards to interventions and the high prevalence of adolescent substance misuse in the Western Cape, exploring these needs within the country's context is warranted and necessary. Design and data collection – This was a qualitative study and data for the study was collected in two main phases: through focus group discussions to identify caregivers needs and to explore perceptions of the intervention; and post-intervention interviews with caregivers and adolescents at a 1-month follow-up session. Findings – Template analysis revealed six main themes: 1) Access to knowledge about substance misuse; 2) Parenting skills; 3) Sources of emotional support; 4) Empowerment for female caregivers; 5) Financial concerns; and 6) Alternative solutions to adolescent's involvement in the justice system. Caregivers also reported various feelings that are a direct result of their experiences. Discussion – Caregivers have distinct needs that require designated responses, however, some of these needs can be addressed through their inclusion in treatment interventions for adolescents who misuse substances.